2012
DOI: 10.1016/j.juro.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Priapism is Associated with Sleep Hypoxemia in Sickle Cell Disease

Abstract: Oxyhemoglobin desaturation during sleep was associated with priapism history. It may underlie the distribution pattern of penile rigidity events during sleep in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Several studies have shown that nocturnal hypoxemia is associated with higher morbidity in SCD manifesting as higher degree of anemia and lower cumulative annual average hemoglobin levels [24,25], increased pulmonary artery pressures [26], worse pulmonary function tests [25], increased left ventricular (LV) hypertrophy and LV diastolic dysfunction [27], increased incidence of priapism [28], and nocturnal enuresis [29], more frequent painful [30] and vaso-occlusive crises in general, increased incidence of CNS events [31], worse executive cognitive function [32] and even vitamin C deficiency, suggestive of reduced anti-oxidant capacity [33].…”
Section: Nocturnal Hypoxemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that nocturnal hypoxemia is associated with higher morbidity in SCD manifesting as higher degree of anemia and lower cumulative annual average hemoglobin levels [24,25], increased pulmonary artery pressures [26], worse pulmonary function tests [25], increased left ventricular (LV) hypertrophy and LV diastolic dysfunction [27], increased incidence of priapism [28], and nocturnal enuresis [29], more frequent painful [30] and vaso-occlusive crises in general, increased incidence of CNS events [31], worse executive cognitive function [32] and even vitamin C deficiency, suggestive of reduced anti-oxidant capacity [33].…”
Section: Nocturnal Hypoxemiamentioning
confidence: 99%
“…Despite the above mentioned association of priapism with hypoxemia, and the fact that priapism occurs mainly at night in SCD, these associations have not received major attention until recently. In a caseecontrol study by Roizenblatt and colleagues [28], 34 adults with SCD were evaluated with a PSG for the presence of sleep disorder and were also assessed for penile rigidity during sleep. Of the 34 patients, 18 patients had a positive history of priapism in the preceding year, while 16 were matched controls, with all subjects being non-obese and without evidence of severe SCD comorbidities.…”
Section: Priapismmentioning
confidence: 99%
“…Indeed, objective assessment of sleep in SCD indicates a phenotype of increased arousal frequency and reduced total sleep time [4]. The high prevalence of OSAS in SCD patients would be expected to fragment sleep, and other chronic conditions common in SCD, such as enuresis [18], priapism [19], and periodic leg movement disorder [20], would also be expected to fragment rather than consolidate sleep. Yet, in young Townes mice, the SS genotype infers a distinctive phenotype where NREM sleep is reduced, but paradoxically consolidated.…”
Section: Discussionmentioning
confidence: 99%
“…High PLMS indexes are associated with dopaminergic disorders. However, few studies on PLMS in adults have been published (Roizenblatt et al, 2012;Sharma et al, 2015). However, nonspecific changes have been demonstrated, such as in relation to heart rate and blood pressure (Hornyak et al, 2006).…”
mentioning
confidence: 99%
“…PLMS has been correlated with attention deficit disorder and restless leg syndrome in SCD children (Rogers et al, 2011). Sleep disorders also seem to be important in adults with SCD, but only two studies have made any observations in relation to PLMS (Roizenblatt et al, 2012;Sharma et al, 2015). Roizenblatt et al (2012) noted an association between PLMS and history of priapism in a group of 34 adults with SCD.…”
mentioning
confidence: 99%